2019
DOI: 10.3390/agronomy9090516
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and Stability Comparisons of Inbred and Hybrid Cotton in Yield and Fiber Quality Traits

Abstract: Cotton (Gossypium hirsutum L.) is the most important fiber crop worldwide. Characterizing genotype by environment interaction (GEI) is helpful to identify stable genotypes across diverse environments. This study was conducted in six environments to compare the performance and stability of 11 inbred lines and 30 intraspecific hybrids of cotton. Analysis of variance using the additive main effects and multiplicative interaction model revealed that genotype (G), environment (E), and GEI had highly significant eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

6
4

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 46 publications
1
32
0
2
Order By: Relevance
“…Our previous study of 11 inbred lines and 30 intraspecific hybrids in six environments found that cotton hybrids had better and stable performance compared to inbred lines in yield traits [40]. Here, analysis of heterosis in these hybrids showed majority of hybrids had positive mid parent heterosis (MPH) and better parent heterosis (BPH) for boll weight, seed cotton yield (SCY), lint yield and lint percentage (Additional file 14: Table S1).…”
Section: Identification Of Cotton Hybrids Exhibiting Different Level mentioning
confidence: 80%
“…Our previous study of 11 inbred lines and 30 intraspecific hybrids in six environments found that cotton hybrids had better and stable performance compared to inbred lines in yield traits [40]. Here, analysis of heterosis in these hybrids showed majority of hybrids had positive mid parent heterosis (MPH) and better parent heterosis (BPH) for boll weight, seed cotton yield (SCY), lint yield and lint percentage (Additional file 14: Table S1).…”
Section: Identification Of Cotton Hybrids Exhibiting Different Level mentioning
confidence: 80%
“…Cotton ( Gossypium hirsutum L.), as a vital resource for plant fiber and oil, is widely cultivated worldwide [1]. However, its low yield is one of the key factors hindering its further development.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study of 11 inbred lines and 30 intraspeci c hybrids in six environments found that cotton hybrids had better and stable performance compared to inbred lines in yield traits [40]. Here, analysis of heterosis in these hybrids showed majority of hybrids had positive mid parent heterosis (MPH) and better parent heterosis (BPH) for boll weight, seed cotton yield (SCY), lint yield and lint percentage (Table S1).…”
Section: Identi Cation Of Cotton Hybrids Exhibiting Different Level Omentioning
confidence: 71%